Modeling Marine Tourism from the Perspective of Sustainable Tourism in Serangan Tourism Village - Rizki Sumardani; I Gede Wiramatika; Fenny Sengkey; Rosvita Flaviana Osin; I Wayan Agus Anggayana; I Madw Weda Satia Nagara (Politeknik Pariwisata Makassar, 2024)
The study of marine tourism in Serangan Tourism Village from the perspective of sustainable tourism is very important. Still, it faces pressure from tourism development that can threaten environmental sustainability and the welfare of local communities with increasing tourist visits. As for the theoretical basis in this study using sustainable tourism, the method in this study uses qualitative research methods, the research location of the research was carried out in the tourist village of Serangan Bali, the method of collecting data in this study by conducting observations, interviews, and documentation, and data analysis in this study using qualitative descriptive with the help of Nvivo 12 software. The results of this study show that in the economic aspect, the business of making environmentally friendly souvenirs is one example of a business such as woven bags from palm leaves, jewelry from shells, and handicrafts from bamboo. Socio-cultural aspects unique traditions and cultures can be introduced to tourists, thus broadening the community's horizons and benefiting from new ideas and practices that can improve the quality of life and strengthen social relationships between communities and tourists visiting Serangan Tourism Village. The environmental aspect of increased education and environmental awareness is very important. Constant efforts are to educate tourists and the local community about saving energy and reducing waste. Therefore, the village is not only a beautiful tourist destination but also an example of sustainable tourism development that considers environmental sustainability a top priority in reducing the various potential negative impacts of tourism on the environment.